Pengaruh Pendidikan Kesehatan terhadap Stigma Masyarakat Tentang Infertilitas di Kelurahan Silaberanti Palembang - Ayu Enjellya; Suzanna Suzanna; Ayu Dekawaty (IKesT Muhammadiyah Palembang, 2024)
Background : . Infertility is one of the most significant global health problems affecting millions of people of reproductive age, both men and women worldwide. Infertility is a condition of the reproductive system that fails to conceive after 12 months or more of marriage and regular sexual intercourse without using contraception. Research Objectives: To determine the effect of health education on the community's stigma about infertility in the Silaberanti Village of Palembang. Type of Research: Pre-experimental with a one group pre-test post-test design. The research subjects were 67 people in RT 06 Silaberanti Palembang Village. The research was conducted in June 2023. The results of data analysis were tested using the Wilcoxon test. Research Results: Statistical results show that there is an effect of health education on community stigma about infertility with a p-value (0.000) <0.05. Conclusion: Health education is effectively used to reduce the negative stigma in society about infertility. Keywords: Infertility, Health Education, Community Stigma